STRUKTUR INFORMASI PADA KLAUSA BAHASA MINANGKABAU Sebuah telaah tipologi grammatical dan struktur informasi - Jufrizal Jufrizal; Rusdi Rusdi; Lely Refnita (English Department FBS UNP, 2009)
There are three types of clause in Minangkabaunese based on the typological analysis, namely: active, passive, and topicalization one. Accordingly, each clause has special information structure which makes they are different in communicating messages. This article tries to describe the types of clauses in Minangkabaunese based on typological analysis and then the discussion is continued in order to know the information structure in each clause. This article is derived and developed based on the result of a fundamental research conducted for the first year (2008) in West-Sumatra.